Monte Carlo Simulation to Determine Deposition Ratio of Dosage in a-SI Epid with Dose Deposition on Water - Herwiningsih, Sri; Rianto, Sugeng; Yuana, Firdy (Natural B, Journal of Health and Environmental Sciences, 2014)
The study aimed to explore the use of a-Si EPID as a dosimeter for IMRT delivery. The main objective of the study was to determine the ratio of dose deposited in a-Si EPID and the dose deposited in water. Linac used in the simulation was Electa Precise Linac and A-Si EPID model used in the study was based on the configuration of iView GT Elekta a-Si EPID. Study the characteristic of energy deposition at a-Si EPID and water detector shows that the energy deposition at a-Si EPID detector is higher than that of water detector at low photon energy (<0.1 MeV). This is caused by an enhancement of photoelectric interaction between photon beam and a-Si EPID detector at low energy X-rays. The simulation of dose deposition by using square fields show that the ratio between the dose deposition of a-Si EPID and the dose deposition of water detector (α) increases with an increase of the field size. The value of α ranges from 0.60 – 0.66. The similar result was shown in the simulation of dose deposition by using IMRT beam, in which the value of α ranges from 0.63 – 0.64. The α value is useful to relate the measured dose from detector to the equivalent dose of water, which is often used as a reference medium in radiotherapy dosimetry.